From divergent to convergent plates: Resulting facies shifts along the southern and western margins of the Sino-Korean Plate during the Ordovician. (September 2019) - Yang, Renchao; van Loon, A.J. (Tom); Jin, Xiaohui; Jin, Zhijun; Han, Zuozhen; Fan, Aiping; Liu, Quanyou
Highlights: The setting of the SW part of the Sino-Korean Plate changed from diverging to converging. The process took place in the Middle-Late Ordovician. The transition from diverging to converging resulted in shifts of the sedimentary facies. Analysis of the facies shifts results in a 3-D model of the change from a diverging to a converging regime. Abstract: During the Middle to Late Ordovician, the Sino-Korean Plate changed its movement from diverging to converging along its southern and western margins. This resulted in shifts of the sedimentary facies in the Ordos Basin: the environment changed from carbonate platforms in an epeiric sea to deep-sea slopes and a deep-sea basin. This had more than regional consequences: the area is not only the key for understanding the evolution of the tectonic activity and sedimentary environment of the Sino-Korean Plate, but also for a better insight into the structural history of the Yangtze Plate, and the Qinling Orogene and the Qilian Orogene. In addition to autochthonous sediments, slumps, debrites, turbidites and contourites are present, as found both in the field and in drilling cores. The lithological successions allow, in combination with well-logging data, facies correlations of the Ordovician rocks. It appears that the sedimentary facies along the southern and western margins of the Sino-Korean Plate show distinct shifts during the Middle-Late Ordovician. These facies shifts were a consequence of the change in the tectonic regime of the basin from divergence to convergence. A 3-D structural and depositional model of the passive plate margin and carbonate platform within its finally compressive setting is compared with the model of the ocean-trench/island arcs/back-arc rift basin/slope/platform in its initial tensional setting. These models illustrate the change of the structural regime in combination with the resulting shifts in sedimentary facies. The present contribution thus provides a link between geodynamics and sedimentary basin filling.